PENGARUH STANDAR OPERASIONAL PROSEDUR TERHADAP KUALITAS PELAYANAN ROOM ATTENDANT PADA ALAM BOUTIQUE RESORT UMALAS SEMINYAK - A.A. Istri Ngurah Dyah Prami; Ni Putu Widiasturi; I Kadek Ardi Ariestawa (Universitas Triatma Mulya, 2021)
Service quality is the main thing that guests consider, because it concerns the safety and comfort of guests while in a hotel. To maintain the quality of services that a company has, especially those engaged in services, a reference is needed in the form of standard operating procedures. This study aims to determine the effect of standard operating procedures on the quality of room attendant service. The sample in this study were 240 consumers of Alam Boutique Resort Umalas Seminyak. Data analysis using simple linear regression analysis techniques to answer the problem formulation with the help of the SPSS program.The partial test results show that the standard operating procedure has a coefficient value of 0.176, a T-count value of 2.156 and a significance value of 0.032 or less than 0.05. This shows that the variables: 1) Standard Operating Procedures (SOP) have a positive and significant effect on the quality of room attendant services. From the test results the coefficient of determination that SOP affects the quality of service at Alam Boutique Resort Umalas by 61.5% while the remaining 38.5% is influenced by other variables not discussed in this study.